PENGARUH LOCUS OF CONTROL, KOMITMEN ORGANISASI, KINERJA, TURNOVERINTENTION, TEKANAN ANGGARAN WAKTU, GAYA KEPEMIMPINAN DAN KOMPLEKSITAS TUGAS TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - Monica Melsa Yunita Wibowo (Universitas Katolik Soegijapranata Semarang, 2015)
Along with the growing age, the role of auditors are increasingly widespread on the continuity of an organization. Auditor increasingly required to be a professional to be able to organize a good financial governance. An implementation of the professional attitude is to avoid dysfunctional behaviors in the audit of financial statements. Dysfunctional behavior that is very prone to this can be triggered by two factors, namely internal and external. The study will analyze the influence of locus of control, the negative influence of organizational commitment, the negative effect of performance, positive influence turnover intention, positive influence budget pressure, the influence of leadership style and positive influence on the complexity of the task dysfunctional behavior auditor. Using two methods of data collection, the method of a survey conducted on 48 people auditor of Semarang Public Accountant Office, as well as interviews FGD to 9 people auditor of Semarang Public Accountant Office, the results of this study obtained by multiple regression analysis using SPSS which is then amplified and clarified with qualitative data results FGD interview. This study indicates that the locus of control affects the dysfunctional behavior of auditors, while the other variables, organizational commitment, performance, turnover intention, time budget pressure, leadership style, and the complexity of the task has no effect on the auditor dysfunctional behavior. Keywords :